From traditional roots to digital bytes: Can digitalizing ESG improves Ghanaian rural banks' brand equity through stakeholder engagement, and customer loyalty? - Francis Atta Sarpong; Peter Sappor; George Nyantakyi; Isaac Ahakwa; Owusu Esther Agyeiwaa; Benjamin Blandful Cobbinah (Cogent Business & Management, 2023)
This study examines the impact of Digitalized Environmental, Social, and Governance (DESG) practices on rural banks in Ghana, focusing on their relationship with stakeholder engagement, customer loyalty, brand equity, and financial performance. The study collected data from 724 respondents, including bank customers and officials. The study finds that DESG practices directly and positively affect rural banks' brand equity using Partial Least Squares Structural Equation Modeling (PLS-SEM). Additionally, stakeholder engagement indirectly and positively mediates the relationship between DESG and brand equity. Meanwhile, customer loyalty significantly mediates DESG and brand equity, and the combination of stakeholder engagement and customer loyalty jointly and significantly mediates the relationship between DESG and brand equity. Furthermore, DESG and brand equity indirectly and significantly impact rural banks' financial performance during the study. These results underscore the essential role of digitalizing ESG practices in enhancing banks' brand equity and overall performance. As a result, the study recommends that rural banks invest in digital infrastructure and platforms to enable effective stakeholder engagement, customer loyalty programs, and ESG reporting.
Keywords: 650; brand Equity; customer loyalty: Rural Bank; digital transformation: ESG practices; stakeholder engagement